The political economy of the fintech regulation in China and its implications - Zhang, Meihui; Zhang, Chi (Computer law & security review, 2025)
Fintech has seen exponential growth in recent years, breaking into markets often underserved by traditional financial services. Along with fintech's benefits, a series of risks caused by fintech has drawn regulators’ attention globally. Fintech activities can be generally categorised into two parts, namely investment-oriented fintech activities such as peer-to-peer lending, equity crowdfunding, and initial coin offerings; the other is payment-oriented fintech, which includes digital payment and central bank digital currencies. China has been one of the pioneers in promoting fintech markets during the past decade. Given that the former type of fintech will generate distinct investment risks while the latter one's risk is much slighter, China's regulator treats the two kinds of fintech differently. This article examines China's differing regulatory approaches to its investment-oriented and payment-oriented fintech sectors, respectively, and explores market conditions to which the above difference attributes. Beyond China, this article argues that a perfect result cannot be reached by pure external regulation; instead, successful regulation over investment-oriented fintech is significantly subject to the economic foundation of a given jurisdiction, among which maturity of investors is a constraint condition for mitigating risks in investment-oriented fintech industry.